Clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in children in China - Wen Song; Qingwen Shan; Yue Qiu; Xianyao Lin; Chunhui Zhu; Zhiqiang Zhuo; Caihong Wang; Jianning Tong; Rui Li; Chaomin Wan; Yu Zhu; Minxia Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Invasive Salmonella infections result in a significant burden of disease including morbidity, mortality, and financial cost in many countries. Besides typhoid fever, the clinical impact of non-typhoid Salmonella infections is increasingly recognized with the improvement of laboratory detection capacity and techniques. A retrospective multicenter study was conducted to analyze the clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in hospitalized children in China during 2016–2018. A total of 130 children with invasive Salmonella infections were included with the median age of 12 months (range: 1–144 months). Seventy-nine percent of cases occurred between May and October. Pneumonia was the most common comorbidity in 33 (25.4%) patients. Meningitis and septic arthritis caused by nontyphoidal Salmonella (NTS) infections occurred in 12 (9.2%) patients and 5 (3.8%) patients. Patients < 12 months (OR: 16.04) and with septic shock (OR: 23.4), vomit (OR: 13.33), convulsion (OR: 15.86), C-reactive protein (CRP) ≥ 40 g/L (OR: 5.56), and a higher level of procalcitonin (PCT) (OR: 1.05) on admission were statistically associated to an increased risk of developing meningitis. Compared to 114 patients with NTS infections , 16 patients with typhoid fever presented with higher levels of CRP and PCT ( P < 0.05). The rates of resistance to ampicillin, sulfamethoxazole/trimethoprim, ciprofloxacin, and ceftriaxone among Salmonella Typhi and NTS isolates were 50% vs 57.3%, 9.1% vs 24.8%, 0% vs 11.2%, and 0% vs 9.9%, respectively. NTS has been the major cause of invasive Salmonella infections in Chinese children and can result in severe diseases. Antimicrobial resistance among NTS was more common.